2011
DOI: 10.1007/s11738-010-0704-6
|View full text |Cite
|
Sign up to set email alerts
|

Occurence of eugenol, coniferyl alcohol and 3,4,5-trimethoxyphenol in common buckwheat (Fagopyrum esculentum Moench) and their biological activity

Abstract: Common buckwheat (Fagopyrum esculentumMoench) is well known as a weed suppressing crop due to its strong competitive and allelopathic characteristics. The possible allelopathic compounds in buckwheat include compounds from different groups, such as flavonoids, fatty acids, phenolic acids, etc. Less attention has been paid to other phenolic compounds, specifically eugenol, o-eugenol, coniferyl alcohol and 3,4,5-trimethoxyphenol as possible allelochemicals. The effects of eugenol, o-eugenol, coniferyl alcohol, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Tsuzuki and Dong (2003) identified ferulic, caffeic, and chlorogenic acids, as well as fatty acids among the allelochemicals in buckwheat. In other studies, eugenol, coniferyl alcohol, and 3,4,5-trimethoxyphenol were identified in buckwheat stems, leaves, and roots (Kalinova et al 2011). In the above ground parts of buckwheat, Iqbal et al (2002) found the alkaloids fagomine, 4-piperidone, and 2-piperidinomethanol which showed a strong inhibitory effect on lettuce growth.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Tsuzuki and Dong (2003) identified ferulic, caffeic, and chlorogenic acids, as well as fatty acids among the allelochemicals in buckwheat. In other studies, eugenol, coniferyl alcohol, and 3,4,5-trimethoxyphenol were identified in buckwheat stems, leaves, and roots (Kalinova et al 2011). In the above ground parts of buckwheat, Iqbal et al (2002) found the alkaloids fagomine, 4-piperidone, and 2-piperidinomethanol which showed a strong inhibitory effect on lettuce growth.…”
Section: Introductionmentioning
confidence: 77%
“…Buckwheat extracts enhanced the content of phenolic compounds and flavonoids in tomato and maize tissues, which may be related to activation of the defense mechanism to stressful conditions (Szwed et al 2014). There are other compounds in buckwheat that may have allelopathic efficiency (Kalinova et al 2007(Kalinova et al , 2011Szwed et al 2014). It is known that the presence of buckwheat residues in soil can suppress various weeds (Tsuzuki and Dong 2003;Xuan and Tsuzuki 2004;Kato-Noguchi et al 2007;Kumar et al 2008Kumar et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Eugenol was phytotoxic against a range of weeds such as Taraxacum officinale (L.) Weber ex F.H.Wigg. [ 58 ], Amaranthus retroflexus L. [ 59 ], Chenopodium album L. [ 60 ], Echinochloa crus-galli (L.) P.Beauv., Phalaris minor Retz., Ageratum conyzoides (L.) L., Leptochloa chinensis (L.) Nees, Bidens Pilosa L., and Commelina benghalensis L. [ 58 ], being promising as a bio-herbicide.…”
Section: Resultsmentioning
confidence: 99%
“…It has the allelopathic potential with a weak inhibitory effect. According to Kalinova et al (2011), coniferyl alcohol showed a weak inhibitory effect on the germination of Plantago lanceolata L. compared with eugenol. Lauric acid identified from the plant Rehmannia glutinosa was proven to provide inhibitory effect on germination, root length and fresh weight of sesame plants.…”
Section: Chemical Compounds Analysismentioning
confidence: 99%